Volvulus, gangrene and perforation of transverse colon in an antepartum eclamptic pregnant patient post caesarean: a case report - Behura, Jharna; Kumar, Sanjiva; Bagga, Poonam; Sinha, Maruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Transverse colon volvulus leading to gangrene and perforation is an extremely uncommon acute surgical complication in pregnancy and puerperium, with a very high rate of mortality and morbidity. Surgical resection is the only treatment. Authors present a case of a 20 years. old women, with antepartum eclampsia, who underwent caesarean section for fetal distress. She complained of abdominal pain from second post-operative day. The pain increased in severity and on the third postoperative day, she developed sudden abdominal distention and appeared pale. Ultrasound revealed free intraperitoneal fluid suggestive of hemoperitoneum. An emergency laparotomy was performed. There was about a litre of blood in the peritoneal cavity with clots. The caesarean incision site, uterus adnexa and broad ligaments were all intact. On further exploration, volvulus of the transverse colon was seen along with gangrene and perforation of the middle part of transverse colon. Resection of the gangrenous part was done with closure of the distal loop. Proximal loop was brought out as colostomy. The patient had an uneventful postoperative course thereafter and was discharged on regular diet on 12th postoperative day. Volvulus of transverse colon leading to gangrene is rare in pregnancy and puerperium, but must form part of clinician’s differential diagnosis when encountering a patient with persistent abdominal pain and bowel distention. Early diagnosis and timely surgical intervention could significantly improve the outcome of this catastrophic condition.